2016
DOI: 10.1091/mbc.e15-08-0558
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally regulated GTP-binding protein 2 coordinates Rab5 activity and transferrin recycling

Abstract: The small GTPase Rab5 regulates the early endocytic pathway of transferrin (Tfn), and Rab5 deactivation is required for Tfn recycling. Rab5 deactivation is achieved by RabGAP5, a GTPase-activating protein, on the endosomes. Here we report that recruitment of RabGAP5 is insufficient to deactivate Rab5 and that developmentally regulated GTP-binding protein 2 (DRG2) is required for Rab5 deactivation and Tfn recycling. DRG2 was associated with phosphatidylinositol 3-phosphate-containing endosomes. It colocalized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 43 publications
3
26
0
Order By: Relevance
“…To this end, DN mutants of Rab5 (S34N), Rab7 (T22N), and Rab11 (S25N), which have been validated in previously reported entry studies with different enveloped viruses (31,32,57), were employed. The functionality of Rab WT and DN constructs was confirmed in PK-15 cells by using labeled transferrin as a control (31,58). As expected, the overexpression of all three Rab DN constructs reduced the accumulation of transferrin in comparison with cells expressing WT Rab, with minor fluorescence intensity in the cytoplasm and failure in the superposition of both proteins (Fig.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…To this end, DN mutants of Rab5 (S34N), Rab7 (T22N), and Rab11 (S25N), which have been validated in previously reported entry studies with different enveloped viruses (31,32,57), were employed. The functionality of Rab WT and DN constructs was confirmed in PK-15 cells by using labeled transferrin as a control (31,58). As expected, the overexpression of all three Rab DN constructs reduced the accumulation of transferrin in comparison with cells expressing WT Rab, with minor fluorescence intensity in the cytoplasm and failure in the superposition of both proteins (Fig.…”
Section: Resultssupporting
confidence: 67%
“…Because Rab5 depletion affected CSFV entry more than did Rab7 depletion, Rab5 may play a more critical role in CSFV infection. In addition, the functionality of Rab knockdown in PK-15 cells was confirmed by using labeled transferrin as a control (31,58). As expected, silencing of Rab5 or Rab7 reduced the accumulation of transferrin, compared to that in control cells, with minor fluorescence intensity in the cytoplasm and failure in the superposition of both proteins (Fig.…”
Section: Resultssupporting
confidence: 65%
“…Previously, we have reported that DRG2 depletion induces cell cycle arrest and mitochondrial dysfunction , leading to inhibition of cell growth. In addition, it has been reported that DRG2 interacts with Rab5 on early endosome and DRG2 depletion inhibits endosome trafficking , enhances the Akt signal from endosome, and inhibits perinuclear Golgi stacking and cell migration . In this study, we found that DRG2 depletion inhibited growth of melanoma cells.…”
Section: Discussionsupporting
confidence: 58%
“…Previously, we found that overexpression of DRG2 affects cell proliferation and apoptosis in Jurkat human T cells , inhibits T H 17 differentiation, and ameliorates experimental autoimmune encephalomyelitis in mice . We also learned that DRG2 interacts with Rab5 on endosomes and is required for Rab5 inactivation on endosomes and for recycling of transferrin (Tfn) to the plasma membrane . Together, these data demonstrate that DRG2 is an important regulator of signal pathways for cell growth, differentiation, and/or vesicle trafficking.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation